The Effect of Airport Service Quality Performance on Passenger Satisfaction at Juwata Tarakan International Airport - Irwan Faizal; Hemi Pamuraharjo; Ubaedillah Ubaedillah (Eduvest - Journal of Universal Studies, 2025)
Airports have a significant role in supporting the smoothness and comfort of air transportation. The quality of good service performance at the airport is a crucial factor in improving passenger satisfaction. The purpose of the study was to determine the level of performance and the effect of airport service quality on passenger satisfaction at Juwata Tarakan International Airport. Service quality measurement is based on five dimensions, namely: tangibles, empathy, reliability, assurance and responsiveness, which are further elaborated into 37 indicators. Satisfaction is measured based on passenger perceptions based on their interests/expectations and experiences of airport performance. The method used in this research is descriptive quantitative with a survey approach. Data were collected through questionnaires distributed to passengers at Juwata Tarakan International Airport. Data analysis uses statistical tools to find the effect and level of conformity. Meanwhile, to determine the ranking of each service quality indicator using a Cartesian diagram. From data processing and analysis, the results show that there is a positive and significant influence between the quality of airport services on passenger satisfaction. There are 17 indicators that are considered to perform below average, 4 of which are considered important by passengers. This provides implications for airport managers, to further improve their performance, especially on 4 indicators of airport service quality